Serum levels of interleukin-6 and interleukin-8 as diagnostic markers of acute pyelonephritis in children - Abolfazl Mahyar; Parviz Ayazi; Mohammad Reza Maleki; Mohammad Mahdi Daneshi-Kohan; Hamid Reza Sarokhani; Hassan Jahani Hashemi; Mousa Talebi-Bakhshayesh (Korean Pediatric Society, 2013)
PurposeEarly diagnosis and treatment of acute pyelonephritis in children is of special importance in order to prevent serious complications. This study was conducted to determine the diagnostic value of serum interleukin (IL)-6 and IL-8 in children with acute pyelonephritis.MethodsEighty-seven patients between 1 month to 12 years old with urinary tract infection (UTI) were divided into 2 groups based on the result of 99m-technetium dimercapto-succinic acid renal scan: acute pyelonephritis (n=37) and lower UTI (n=50) groups. White blood cell (WBC) count, neutrophil (Neutl) count, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) concentration, platelet count, and serum IL-6 and IL-8 concentrations of both groups were measured and compared.ResultsThere was a significant difference between two groups regarding WBC count, Neutl count, ESR, and CRP concentration (P<0.05). In addition, the difference between the two groups regarding serum IL-6 and IL-8 concentrations was not significant (IL-6, 60 and 35.4 pg/mL and IL-8, 404 and 617 pg/mL, respectively). The sensitivity and specificity of serum IL-6 and IL-8 for diagnosis of acute pyelonephritis were 73%, 42% and 78%, 32%, respectively. Sensitivity, specificity, negative and positive predictive values of serum IL-6 and IL-8 were less than those of acute phase serum reactants such as CRP.ConclusionThis study showed that there was no significant difference between acute pyelonephritis and lower UTI groups regarding serum IL-6 and IL-8 levels. Therefore, despite confirming results of previous studies, it seems that IL-6 and IL-8 are not suitable markers for differentiating between acute pyelonephritis and lower UTI.